Analisis putusan Pengadilan Negeri mengenai Upaya Hukum Perum Bulog atas Tindakan Hukum Wanprestasi yang Dilakukan Oleh Pihak Mitra CV Mulyo Santoso: Tinjauan Kasus terhadap Putusan PN Jakarta Selatan No. 337/PDT.G/2013/PN.JKT.SEL - Nur Rofi Dwianti; Salsa Nabilani; Amelia Vega; Sann Satriatama (Universitas Wahid Hasyim, 2024)
One of the main sources of food for Indonesians is rice. To ensure food security and price stability of rice, the government established an agency called Perum Bulog. Perum Bulog carries out food procurement through grain sales, grain milling supplies, and rice sales. However, in reality, the agreement between Perum Bulog and its partners is inseparable from various challenges and problems. One of them is a default committed by a partner who has an agreement with Perum Bulog. In this research, the problems discussed are Perum Bulog's legal efforts to deal with partner defaults and the directors' responsibility for losses suffered by PERUM BULOG as a result of partner defaults. The purpose of this article is to find out the legal efforts of Perum Bulog for the legal action of default committed by the partner, to analyze the responsibility of the board of directors for the losses suffered by Perum Bulog due to the default of the partner. The method used in this article is normative juridical method and the specification is descriptive analytical. The data source used consists of secondary data which can be divided into primary legal materials and secondary legal materials. The data collection used in the analysis in this article is literature and documentary. The data analysis technique in this research is processed through qualitative analysis. According to the research, the Board of Directors of Bulog has taken legal action based on Article 1243 of the Civil Code to make a statement of acknowledgment of debt by CV Mulyo Santoso and file a claim for compensation to the previous Board of Directors of Bulog. In addition, based on Article 100 Paragraph 2 of Government Regulation No. 13/2016 and Article 97 of the Company Law, the Board of Directors of Bulog can be asked to compensate for the agreement made if it is proven that there is a loss arising from their fault.